METHANE EMISSION FROM DIRECT SEEDED RICE UNDER THE INFLUENCES OF RICE STRAW AND NITRIFICATION INHIBITOR - Sutriswanto, Slamet (Indonesian Journal of Agricultural Science, 2012)
Incorporation of rice straw into soil is a common practice to improve soil productivity and increase inorganic fertilizer availability. However this practice could contribute to methane (CH4) emission; one of the greenhouse gases that causes global warming. Nitrification inhibitors such as neem cake and carbofuran may reduce methane emission following application of rice straw. The study was aimed to evaluate the application of rice straw and nitrification inhibitor to methane emission in rainfed low land rice system.  A factorial randomized block design was used with three replicates. The first factor is rice straw applications (5 t ha-1 fresh straw, 5 t ha-1 composted straw), and the second factor is nitrification inhibitors (20 kg ha-1 neem cake, 20 kg ha-1 carbofuran nematicide). The experiment was conducted at rainfed lowland area in Pati, Central Java during 2009/2010 rainy season. Ciherang variety was planted as direct seeded rice with spacing of 20 cm X 20 in each plot of 4 m X 5 m. The rice straw was treated together with soil tillage, whereas nitrification inhibitor was applied together with Urea application. Parameters observed were methane flux, plant height, plant biomass, grain yield, organic C content, and bacterial population in soil. The methane flux and soil organic C were measured at 25, 45, 60, 75, and 95 days after emergence. The experiment showed that composted rice straw application significantly emitted methane lower (73.2±6.6 kg CH4 ha-1 season-1) compared to the fresh form of rice straw (93.5±4.0 CH4 ha-1 season-1).  The application of nitrification inhibitors neem cake and carbofuran reduced methane emission as much as 20.7 and 15.4 kg CH4 ha-1 season-1, respectively.  Under direct seeded rice system, methane flux level relates with plant biomass as shown by linier regression of Y = 0.0015 X +0.0575 (R2 = 0.2305, n = 27).  This means that higher plant biomass produced more methane flux. The study indicates that application of nitrification inhibitors such as neem cake is more prospective in decreasing methane emission from direct seeded rice cropping because name trees are abundant in eastern parts of Indonesia.